Effects of a Nanoencapsulated Moringa Leaf Ethanolic Extract on the Physiology, Metabolism and Reproductive Performance of Rabbit Does during Summer - Nagwa I. El-Desoky; Nesrein M. Hashem; Antonio Gonzalez-Bulnes; Ahmed G. Elkomy; Zahraa R. Abo-Elezz (MDPI AG, 2021)
This study investigated the effect of Moringa leaf ethanolic extract (MLEE) on heat-tolerance variables and the reproductive performance of rabbit does bred under hot climate conditions. Additionally, the effect of nanoencapsulation technology on the biological efficiency of MLEE was considered. A total of 56 rabbit does were randomly divided into four experimental groups and treated with 50 mg/kg body weight (BW) nonencapsulated MLEE, 25 or 10 mg/kg BW nanoencapsulated MLEE, or not treated (Control, C). The treatments continued for 50 days, including mating and pregnancy times. Physiological and hematochemical variables, hormonal profiles, and reproductive performance (kindling rate and litter characteristics) were determined. The active components of MLEE were identified. The results indicated that MLEE has 30 active components. All MLEE-based treatments reduced heat-stress-related indicators, such as rectal temperatures, respiratory rates and heart rate; improved hematochemical attributes, redox status, and hormones (progesterone and prolactin); and increased the total litter size, the kindling rate, litter size at birth and litter weight at birth. Adding MLEE can alleviate the negative impacts of heat stress by improving metabolism, redox status, and hormonal balance during pregnancy. These effects were seen whether MLLE was in free or encapsulated forms. However, the use of nanoencapsulated MLEE allowed 80% reduction (10 mg/kg BW) in the optimal dose (50 mg/kg BW) without affecting the efficiency of the treatment. These results support the importance of nanoencapsulation technology in improving the bioavailability of active components when they are orally administered.